Teacher literacy skills through minimum competency assessment training - Pramita Yakub; Ahmad Bashri; Sifak Indana; R. Raharjo (Universitas Muhammadiyah Malang, 2022)
Improving the education evaluation system is part of the independent learning policy aiming at encouraging the improvement of quality of learning and learning outcomes in Indonesia. The Ministry of Education and Culture of Indonesia plans the implementation of a national assessment in 2021. Changes to this national assessment evaluate students’ competence and map the education system in the form of inputs, processes, and results that will be achieved. Thus, assessment is no longer an individual assessment. In order to accelerate the improvement of the quality of Indonesian Education, it is necessary to reflect both from the relevant agencies and school agencies as the main actors in the assessment. Based on this thought, it is necessary to carry out training for teachers in compiling AKM problems. The purpose of this study is to find out the implementation of training in preparing minimum competency assessments for teachers, whether there is an increase in teacher literacy skills, and how teachers respond through teacher training. The research method implemented was qualitative descriptive analysis with three stages: preparation, implementation, and evaluation. The results of the minimum competency assessment of teachers are assessed based on the results of the development of AKM MGMP teachers in Surabaya obtained 86% increased results. Training obtained by each MGMP teacher based on the results of AKM workshops were known to be 3 participants gained significant results, it was 38%-46%, while seven other participants ranging from 4%-8% experienced an increase. These results show the success of AKM training activities for teachers. The results of the trainee response provide good and excellent feedback.